Knee Myofascial Pain and Knee-Abdomen Syndromes; A Newly Identified Knee Disorders, Commonly Misdiagnosed as Arthritis, Multiple Case Study - Mohamed, Ibrahim Tobba; Kandil, Olfat A (International Journal of Innovative Research in Medical Science, 2022)
Background: Knee osteoarthritis is a common orthopedic condition. Imaging based pathoanatomical findings are utilized as a cornerstone for diagnosis of the condition, 97% of asymptomatic knees demonstrate pathoanatomical findings, causing doubt of diagnosis and efficiency of intervention based on asymptomatically present pathoanatomical features. Purpose: This study explores myofascial dysfunctions as an alternative explanation to knee pain. Identifying new syndromes termed as knee myofascial pain and knee-abdomen syndromes. Therapeutic intervention: Describing 3 cases of knee osteoarthritis and one case of rheumatoid arthritis treated to full recovery as myofascial dysfunction. All of these cases were investigated and treated to complete recovery from specific myofascial continuity known as deep front line dysfunction, as a cause of knee pain. Results: Both syndromes demonstrated 50% to 100% pain reduction after one session of myofascial release, with no recurrence over long-term follow-up after discharge. Conclusion: Knee myofascial pain and knee-abdomen syndromes are clinically present commonly misdiagnosed as arthritic changes. Myofascial release produced an immediate major pain reduction ranging from 50 to 100%. High quality research is required to identify more accurate diagnostic criteria and consequently best treatment strategies.